NUMERICAL ANALYSIS OF THE IN-CYLINDER FLOW FIELD AND COMPARISON WITH EXPERIMENTAL DATA IN A SINGLE CYLINDER RESEARCH ENGINE - Braga, Raphael Meireles; Reis, Leonardo Mayer; Fonseca, Leonardo Guimarães; Huebner, Rudolf; Valle, Ramon Molina (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
In this paper, the 3D numerical analysis of the flow field in a single cylinder research engine with optical access, running cold flow, is presented. The simulations were carried out in the commercial software Star-CD with es-ICE module and the two different turbulence models: RNG-k-Îµ and k-w SST were compared with experimental data of the engine running at 1000 rpm in motored conditions. A grid independency study is presented using five grids varying from approximately 500,000 to 1,500,000 cells on piston bottom dead center. An optical window inside the engine cylinder was used to measure the velocity components along the crank angle with the PIV technique and a comparison was made with calculated velocity curves. Moreover, a qualitative analysis of the scalar flow field in the region of interest is presented. The results showed a better agreement with the RNG-k-Îµ and experimental mean velocity magnitude curve than k-Ï‰-SST. However, the qualitative scalar velocity field of the k-Ï‰ model captured more details of the flow than the k-Îµ model.